Magnetic resonance imaging Locus Coeruleus abnormality in amnestic Mild Cognitive Impairment is associated with future progression to dementia - Galgani, Alessandro; Lombardo, Francesco; Martini, Nicola; Vergallo, Andrea; Bastiani, Luca; Hampel, Harald; Hlavata, Hana; Baldacci, Filippo; Tognoni, Gloria; De Marchi, Daniele; Ghicopulos, Irene; De Cori, Sara; et al. (European journal of neurology, 2023)
Background and purpose Human neuropathological studies indicate that the pontine nucleus Locus Coeruleus (LC) undergoes significant and early degeneration in Alzheimer's disease. This line of evidence alongside experimental data suggests that the LC functional/structural decay may represent a critical factor for Alzheimer's disease pathophysiological and clinical progression. In the present prospective study, we used Magnetic Resonance Imaging (MRI) with LC‐sensitive sequence (LC‐MRI) to investigate in vivo the LC involvement in Alzheimer's disease progression, and whether specific LC‐MRI features at baseline are associated with prognosis and cognitive performance in amnestic Mild Cognitive Impairment. Methods LC‐MRI parameters were measured at baseline by a template‐based method on 3.0‐T magnetic resonance images in 34 patients with Alzheimer's disease dementia, 73 patients with amnestic Mild Cognitive Impairment, and 53 cognitively intact individuals. A thorough neurological and neuropsychological assessment was performed at baseline and 2.5‐year follow‐up. Results In subjects with Mild Cognitive Impairment who converted to dementia (n = 32), the LC intensity and number of LC‐related voxels were significantly lower than in cognitively intact individuals, resembling those observed in demented patients. Such a reduction was not detected in Mild Cognitive Impairment individuals, who remained stable at follow‐up. In Mild Cognitive Impairment subjects converting to dementia, LC‐MRI parameter reduction was maximal in the rostral part of the left nucleus. Structural equation modeling analysis showed that LC‐MRI parameters positively correlate with cognitive performance. Conclusions Our findings highlight a potential role of LC‐MRI for predicting clinical progression in Mild Cognitive Impairment and support the key role of LC degeneration in the Alzheimer clinical continuum. The Magnetic Resonance Imaging features of Locus Coeruleus (LC) at baseline in Mild Cognitive Impairment subjects converting to dementia at follow‐up (cMCI) differ from those of non‐converting ones (ncMCI). This is specifically related to rostral LC and is more evident in the left LC. ADD, Alzheimer's disease dementia; HC, cognitively intact healthy controls.